(untitled) (Dialogos, 2018)
Resumo. O presente artigo traz como questão central a análise dos discursos médicos em torno da eugenia e do rejuvenescimento no início do século XX, no Brasil. Pretende sublinhar a participação brasileira num projeto de elevação racial e de construção de uma nação superior, quer por meio do controle dos chamados fracos e degenerados, quer pela possibilidade que se dizia abrir na reconstituição física, mental e moral de parte de sua população. Nesse sentido aqui se estabelece um diálogo com estudos atuais sobre a noção de saúde e as permanências históricas em torno da idéia de rejuvenescimento e da busca de um “novo homem” geneticamente modificado como símbolo da saúde da população. Abstract. The central issue of the present article is the analysis of medical discourse on eugenics and rejuvenation at the turn of the 20th century in Brazil. It intends to emphasize Brazilian participation in a project involving racial elevation and the construction of a superior nation, either, by controlling the so-called weak and degenerates, or by reconstituting part of its population physically, mentally, and morally. In this sense, a dialogue is established herein with current studies on the notion of health and historical continuities with respect to the idea of rejuvenation and the search for a genetically modified ‘new man’ as a symbol of the entire population’s health.